Biomechanical behavior of titanium, cobalt-chromium, zirconia, and PEEK frameworks in implant-supported prostheses: a dynamic finite element analysis - Dilara Sahin Hazir; Irem Sozen Yanik; M. Baris Guncu; R. Senay Canay (BMC Oral Health, 2025)
Abstract Background The mechanical properties of framework materials significantly influence stress distribution and the long-term success of implant-supported prostheses. Although titanium, cobalt-chromium, zirconia, and polyether ether ketone (PEEK) are widely used, their biomechanical performance under dynamic loading conditions remains insufficiently investigated. This study aimed to evaluate the biomechanical behavior of four framework materials with different Young's modulus using dynamic finite element stress analysis. Methods A 3D edentulous maxillary model was extracted from a computer tomography (CT) database. Bone level implants with conical connection designs were placed in the anterior (canine) and posterior (first molar) areas. Anterior implants were parallel, yet posterior implants were inclined distally by 30 degrees. According to the framework material, four groups were formed: cobalt-chromium (Co-Cr), zirconia (Zr), titanium (Ti), and polyether ether ketone (PEEK). For each framework material, twelve separate models of analysis were created by applying force in three different orientations. Dynamic forces were employed to replicate the chewing process. Principal and von Mises stresses were measured and evaluated. Results The PEEK framework exhibited the highest maximum von Mises stress values (372.55 MPa) on the abutment and the highest maximum principle stress values (59.27 MPa) in the cortical bone. The Co-Cr framework had the lowest minimum principle stress (3.98 MPa) in the trabecular bone. The displacements of the Co-Cr, Zr, Ti, and PEEK frameworks were 0.15 mm, 0.15 mm, 0.17 mm, and 0.35 mm, respectively. Conclusion Frameworks having a greater Young's modulus are less susceptible to deformation.